Aachen smoking cessation and harm reduction (ASCHR) trial study protocol - scientific evaluation of a psychological-telemedical counseling concept for smoking cessation in patients with vascular diseases - Sebastian Scheliga; Mara Derissen; Knut Kröger; Rainer Röhrig; Lea Schomacher; Hannah Schick; Rainer Beckers; Hinrich Böhner; Ute Habel (BMC, 2024)
Abstract Background Smoking is a major risk factor of cardiovascular diseases, notably peripheral arterial disease (PAD). Despite this link, research on smoking cessation interventions in PAD patients remains scarce and inconclusive regarding the efficacy of such interventions. Therefore, elucidating it is crucial and should address both individuals who smoke that are motivated to quit and individuals who smoke heavily lacking the motivation to quit. Methods/Design The Aachen Smoking Cessation and Harm Reduction (ASCHR) trial is a prospective randomized controlled study (RCT) on the benefits of telemedical-psychological support for smoking cessation in patients with PAD, funded by the "Innovation Fund" of the Joint Federal Committee in Germany. This trial aims to scientifically assess the efficacy, feasibility, acceptance, and efficiency of a multi-stage smoking cessation program based on the recommendations of the German guideline for smoking cessation tailored to patients with PAD, compared to a control group receiving no intervention. Central to the program is psychological counseling utilizing motivational interviewing techniques, delivered through telemedicine via video consultations. The primary endpoint of the ASCHR trial is the smoking cessation rate after 8 months of intervention, with a secondary endpoint evaluating sustained abstinence at a further 6 months follow-up. Smoking cessation is defined as a carbon monoxide level in exhaled air of less than 6 ppm. We hypothesize that the group receiving the multi-stage cessation program will yield a cessation rate at least 10 percentage points higher than that of usual care. Anticipating a dropout rate of around 35%, the planned sample size is at least N = 1032 study participants. Discussion Should the trial demonstrate significant positive outcomes, efforts should be made to integrate the program into routine care in Germany, potentially offering a promising base for future smoking cessation support among PAD patients.